2009
DOI: 10.1088/0004-6256/137/3/3558
|View full text |Cite
|
Sign up to set email alerts
|

RED SUPERGIANTS AS POTENTIAL TYPE IIn SUPERNOVA PROGENITORS: SPATIALLY RESOLVED 4.6 μm CO EMISSION AROUND VY CMa AND BETELGEUSE

Abstract: We present high-resolution 4.6 µm CO spectra of the circumstellar environments of two red supergiants (RSGs) that are potential supernova (SN) progenitors: Betelgeuse and VY Canis Majoris. Around Betelgeuse, 12 CO emission within ±3 ′′ (±12 km s −1 ) follows a mildly clumpy but otherwise spherical shell, smaller than its ∼55 ′′ shell in K i λ7699. In stark contrast, 4.6 µm CO emission around VY CMa is coincident with bright K i in its clumpy asymmetric reflection nebula, within ±5 ′′ (±40 km s −1 ) of the star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(187 citation statements)
references
References 126 publications
(175 reference statements)
7
179
1
Order By: Relevance
“…For instance, van Loon et al (2005) obtained that dust-enshrouded RSGs present mass-loss rates that are a factor of 3-50 times higher than the rate of de Jager et al (1988). Humphreys et al (1997Humphreys et al ( , 2005 and Smith et al (2009) also indicated that the RSG star VY CMa went through important episodic mass ejections 500-1000 years ago. Moriya et al (2011) reached similar conclusions, studying the luminosity curve of SNe with RSG progenitors.…”
Section: Discussion Of Various Possible Origins For the Low-luminositmentioning
confidence: 99%
“…For instance, van Loon et al (2005) obtained that dust-enshrouded RSGs present mass-loss rates that are a factor of 3-50 times higher than the rate of de Jager et al (1988). Humphreys et al (1997Humphreys et al ( , 2005 and Smith et al (2009) also indicated that the RSG star VY CMa went through important episodic mass ejections 500-1000 years ago. Moriya et al (2011) reached similar conclusions, studying the luminosity curve of SNe with RSG progenitors.…”
Section: Discussion Of Various Possible Origins For the Low-luminositmentioning
confidence: 99%
“…3) shows a very extended (≈5 in diameter) asymmetric dusty envelope, with extensions in the southwestern, northwestern and northeastern directions, similar to the positions of the three plumes we observed with NACO. Smith et al (2009) recently found a mildly clumpy, spherical shell around Betelgeuse in CO emission, from spatially resolved spectroscopy at λ ≈ 4.6 μm. Some interesting structures were detected ≈1 west of the star, but their identification to a mass loss event or envelope asymmetry is unclear.…”
Section: Previous High Angular Resolution Observationsmentioning
confidence: 98%
“…Although the extended envelope of Betelgeuse is thought to be inhomogeneous and asymmetric close to the star, on much larger scales, and more importantly on the scales that we are interested in, the outflow is largely spherically symmetric (Smith et al 2009). Furthermore, as discussed in Harper (2010), the massloss mechanism for M supergiant winds is not well understood.…”
Section: The Stellar Windmentioning
confidence: 98%